Prognostic value of preoperative plasma fibrinogen levels in resected stage I non‐small cell lung cancer. Issue 10 (12th April 2022) - Mitsui, Suguru; Tanaka, Yugo; Doi, Takefumi; Hokka, Daisuke; Maniwa, Yoshimasa
Abstract: Background: The number of surgical procedures has increased among patients with early‐stage lung cancer. If the poor prognostic factors for stage I non‐small cell lung cancer (NSCLC) can be simply validated preoperatively, appropriate treatment will be provided. The current study aimed to evaluate the prognostic value of preoperative plasma fibrinogen levels in patients with resected stage I NSCLC. Methods: We retrospectively analyzed the clinicopathological information of patients ( n = 149) who underwent lobectomy for stage I NSCLC between May 2014 and July 2016. Data about peripheral blood analysis, histopathological finding, and follow‐up assessment results were collected from the databases. Patients were divided into the low and high fibrinogen groups. Univariate and multivariate analyses were performed to evaluate the predictors of recurrence and survival. Results: Compared with the low fibrinogen group (<377 mg/dl), the high fibrinogen group (≥377 mg/dl) had a significantly greater number of male participants ( p = 0.04), smokers ( p < 0.001), and those with elevated cytokeratin antigen levels ( p = 0.04), lymphatic invasion ( p = 0.007), and squamous cell carcinoma ( p < 0.001). Plasma fibrinogen level was considered a significant independent factor for recurrence and overall survival on both the univariate and multivariate analyses ( p < 0.001 and p = 0.010) and the multivariate analysis alone ( p = 0.020 and p < 0.012). Conclusion: Preoperative plasma fibrinogen level might be a useful predictor of recurrence and survival in patients with stage I NSCLC. The treatment strategy for patients with high fibrinogen levels could be cautiously considered preoperatively. Abstract : The 5‐year recurrence‐free survival rates of the low and high fibrinogen groups were 85.7% and 55.6%, respectively. The 5‐year overall survival rates were 91.8% among patients with low fibrinogen levels and 70.6% among patients with high fibrinogen levels. Fibrinogen level was considered a significant independent factor for recurrence and overall survival on both the univariate and multivariate analyses ( p < 0.001 and p = 0.010) and the multivariate analysis alone ( p = 0.020 and p < 0.012).